Large aortic aneurysm and dissection in a patient with Marfan’s syndrome - Pivatto Júnior, Fernando; Ramos, Leila Denise Cardoso; Foppa, Murilo; Torres, Felipe Soares (Clinical and Biomedical Research, 2015)
Marfan’s syndrome is an autosomal dominant disorder of connective tissue affecting approximately1 in5000 people. In individuals with this syndrome, more than 90% of deaths from known causes result from cardiovascular complications, such as aortic dissection, aortic regurgitation, and congestive cardiac failure. In this report, we present a patient with a large symptomatic aortic aneurysm and chronic dissection, severe aortic regurgitation and cardiomegaly, treated successfully with resection of the proximal aorta and placement of a mechanic aortic valved graft.